2021
DOI: 10.1080/17549507.2021.1953592
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia management: Does structured training improve the validity and reliability of cervical auscultation?

Abstract: Purpose: Cervical auscultation (CA) uses a stethoscope or microphone to complement the clinical swallow examination by interpreting swallowing sounds and swallow-respiratory coordination. This study investigated the effects of structured CA training on CA-rating agreement with Flexible Endoscopic Evaluation of Swallowing (FEES) and CA rater reliability. Method: Thirty-nine speech-language pathologists participated in a structured CA training course at Gothenburg University. They rated nine swallow-respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 41 publications
1
11
1
1
Order By: Relevance
“…We believe that the limited printed guidance associated with the survey and the lack of formal reviewer training prior to survey use may have affected inter-rater agreement and contributed to the larger number of records that did not pass qualification and verification. In general, structured rater instructions and training improve agreement and validity in a variety of assessments, ranging from radiographic or other clinical measurements to those relying on survey instruments (12,13). When looking at the 123 records that did pass qualification and verification questions by both reviewers, there was substantial inter-rater agreement with respect to total survey quality points.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the limited printed guidance associated with the survey and the lack of formal reviewer training prior to survey use may have affected inter-rater agreement and contributed to the larger number of records that did not pass qualification and verification. In general, structured rater instructions and training improve agreement and validity in a variety of assessments, ranging from radiographic or other clinical measurements to those relying on survey instruments (12,13). When looking at the 123 records that did pass qualification and verification questions by both reviewers, there was substantial inter-rater agreement with respect to total survey quality points.…”
Section: Discussionmentioning
confidence: 99%
“…It therefore should be not used as a standalone instrument for diagnosis of dysphagia. Yet, in a more recent study reported by Bergström and Cichero (2021), with structured training, both validity and reliability of cervical auscultation for dysphagia carried out by speech and language therapists were significantly improved.…”
Section: Introductionmentioning
confidence: 90%
“…A one-hour consensus training was developed by the authors, based on previous research [12,[18][19][20][27][28][29][30] and sent to all raters who were required to rate if the swallowrespiratory sequences were safe and/or dysphagic. See Online Resource 3 as an example of consensus training information regarding swallow-respiratory sound interpretation.…”
Section: Cervical Auscultation Ratingmentioning
confidence: 99%
“…Recent work by Bergström & Cichero [12] identified that early CA studies, often reported poorer CA validity and reliability results [23][24][25][26]. These CA studies were conducted with suboptimal methodology, including (1) poor swallow-respiration sound and sampling methodology, (2) inconsistent/no CA training, (3) variable assessment parameters/ratings for CA versus instrumental assessment, and (4) no provision of definitions − all critical factors for robust research within CA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation